ANALISIS PERBEDAAN PENGGUNAAN KELAS BUFFEREDREADER DAN KELAS SCANNER DALAM PROSES INPUT KEYBOARD PADA PEMROGRAMAN JAVA BERBASIS TEXT - Dikwan Moeis; Sry Yunarti (P3M STMIK Profesional Makassar, 2021)
This study aims to provide a clear picture of the location of the differences in functions and the use of source code from the BufferedReader class and the Scanner class in the input process through the keyboard in Java programming. To know the location of the differences in functions and the use of source code of the two classes, the method used in this study is to make a test design as a reference in the analysis, then the design is poured in the form of a simple program prototype. This study obtained the results in the form of tables, namely the table of differences in the BufferedReader class and the Scanner class, and a prototype of a simple program for the input process through the keyboard.